2023
DOI: 10.3390/wevj14090233
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Design and Analysis of Steering Knuckle of Formula Student Car Using Topology Optimization Method

Ammarul Hasan,
Cunhao Lu,
Wei Liu

Abstract: The steering knuckle is a crucial component of student racing vehicles, designed by the Formula Society of Automotive Engineers (FSAE). Developing a lightweight (LW) vehicle that meets the requirements of the student formula car presents a challenge. This study presents a LW design of the steering knuckle using the Topology Optimization (TO) approach for the Formula Society of Automotive Engineers (FSAE) competition considering two different mass constraints (40% and 48%). Moreover, the research includes Stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this paper, topology optimization is adopted to achieve the lightweight design of the boss. Topology optimization is a design method to determine the optimal structural type, which aims to minimize the weight of the structure while maintaining its performance and strength by redistributing the layout of materials and has been widely used in the field of engineering design [36,37].…”
Section: Experimental Verificationmentioning
confidence: 99%
“…In this paper, topology optimization is adopted to achieve the lightweight design of the boss. Topology optimization is a design method to determine the optimal structural type, which aims to minimize the weight of the structure while maintaining its performance and strength by redistributing the layout of materials and has been widely used in the field of engineering design [36,37].…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Recently, additive manufacturing has been explored for producing high-quality and reliable knuckles [21]. Kim et al [22] performed a finite element study of an additive manufacture steering knuckle for an electric vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that every 10% reduction in vehicle mass, fuel consumption can be reduced by 6%–8%, and exhaust emissions will be reduced by 5%–6%, which achieves the effect of energy saving and emission reduction and promotes the development of automobile lightweight to some extent. 1 At present, the main ways to achieve lightweight usually include structural optimization, 2–9 new materials, 10 and new processes. 11 Among them, Liang et al 2 optimized the structure of a gearbox under multiple load conditions, and the results showed that the mass of optimized gearbox was reduced by 7.6% compared with the initial model, the strength and stiffness were not weakened, and the first and second-order natural frequencies increased about 4.1% and 5.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%